Nanodiamond as a Cytokine Sponge in Infectious Diseases - Yoo, Wonbeak; Lee, Wonhwa; Kim, Hong Nam; Jeong, Jiyoung; Park, Hee Ho; Ahn, June Hong; Jung, Dana; Lee, Juheon; Kim, Ji-su; Lee, Seung Whan; Cho, Wan-Seob; Kim, Seokho (Frontiers in Bioengineering and Biotechnology, 2022)
Cytokine release syndrome (CRS) is a systemic inflammatory response resulting in overexpression of cytokines in serum and tissues, which leads to multiple-organ failure. Due to rapid aggravation of symptoms, timely intervention is paramount; however, current therapies are limited in their capacity to address CRS. Here, we find that the intravenous injection of highly purified detonation-synthesized nanodiamonds (DND) can act as a therapeutic agent for treating CRS by adsorbing inflammatory cytokines. Highly purified DNDs successfully inactivated various key cytokines in plasma from CRS patients with pneumonia, septic shock, and coronavirus disease 2019 pandemic (COVID-19). The intravenous injection of the DND samples in a mouse sepsis model by cecal ligation and puncture significantly improved survival rates and prevented tissue damage by reducing the circulating inflammatory cytokines. The results of this study suggest that the direct injection of highly purified DND into the bloodstream can provide survival benefits for CRS patients by adsorbing inflammatory cytokines.